POLA PENYEBARAN SALINITAS PADA AKUIFER PANTAI PASIR PANJANG, KOTA KUPANG, NTT - Judi K. Nasjono (Environmental Research Center (PPLH) of Udayana University, 2010)
For water demand, people use dug well getting groundwater stored in aquifer at Pasir Panjang, Kecamatan Kelapa Lima, Kota Kupang, NTT. It situated close to Kupang Bay. Thus the aquifer potentially being seawater intrusion when excessive groundwater pumping. Pattern of groundwater salinity distribution is important data for groundwater management. In this study we applied Electric Conductivity (EC) method to measure saline in dug wells. Location, deep of well and groundwater table data took also. Linier regression analysis show that low salinity found on dug well far from coastline and high saline found nearby coastline. The map with contour line show spatial distribution which different on western and eastern of map. Indicating that high intrusion happened on eastern